2009
DOI: 10.1007/s10071-009-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

Keeping track of time: evidence for episodic-like memory in great apes

Abstract: Episodic memory, as defined by Tulving, can be described in terms of behavioural elements (what, where and when information) but it is also accompained by an awareness of one’s past (chronesthesia) and a subjective conscious experience (autonoetic awareness). Recent experiments have shown that corvids and rodents recall the where, what and when of an event. This capability has been called episodic-like memory because it only fulfils the behavioural criteria for episodic memory. We tested seven chimpanzees, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(155 citation statements)
references
References 57 publications
4
147
2
2
Order By: Relevance
“…The field of comparative psychology, in contrast, investigates the evolutionary origins of human cognition via research with humans' closest living relatives, non-human primates, as well as other species of evolutionary interest. This field has shown that many primate species exhibit an array of complex abilities previously thought to be unique to humans, including reasoning about others' perceptions and knowledge, episodic memory and planning, and the ability to use and create complex tools Flombaum and Santos, 2005;Humle and Matsuzawa, 2002;Martin-Ordas, Haun, Colmenares, and Call, 2009;Mulcahy and Call, 2006;Seed and Byrne, 2010) Both developmental and comparative approaches have therefore been critical in generating and testing hypotheses regarding the origins of human-unique cognition. Yet little attention has been paid to the intersection of developmental and comparative inquiry: studies of cognitive development across species.…”
Section: Introductionmentioning
confidence: 99%
“…The field of comparative psychology, in contrast, investigates the evolutionary origins of human cognition via research with humans' closest living relatives, non-human primates, as well as other species of evolutionary interest. This field has shown that many primate species exhibit an array of complex abilities previously thought to be unique to humans, including reasoning about others' perceptions and knowledge, episodic memory and planning, and the ability to use and create complex tools Flombaum and Santos, 2005;Humle and Matsuzawa, 2002;Martin-Ordas, Haun, Colmenares, and Call, 2009;Mulcahy and Call, 2006;Seed and Byrne, 2010) Both developmental and comparative approaches have therefore been critical in generating and testing hypotheses regarding the origins of human-unique cognition. Yet little attention has been paid to the intersection of developmental and comparative inquiry: studies of cognitive development across species.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we examine the three main approaches used to study the memory for events in context: ( (16)]. This approach has also been adapted to many mammalian species, including rats (14,(17)(18)(19), mice (20), meadow voles (21), pigs (22), nonhuman primates (23,24), and humans (25,26). It is important to note that the structure and flexibility criteria have been much less investigated than the content criterion so it remains to be determined whether all these species will meet all three behavioral criteria.…”
Section: Episodic Memory Capacity Across Speciesmentioning
confidence: 99%
“…A study using the same procedure as the one reported here showed that apes did remember the location of a reward after 1 or 2 h RIs [23]. However, unlike the subjects tested here, those subjects remained in the testing room during the RI, which may have minimized interference by other activities in making memories temporarily inaccessible [9,24].…”
Section: Discussionmentioning
confidence: 99%